Mapping Stakeholder User Journeys in Academic Library Research Consultation Services: Identifying Service Gaps and Improvement Opportunities - Haryanto Haryanto; Dwi Cahyo Yanuargo; Sri Haryati; Dian Hapsari (FKIP - Universitas Riau, 2026)
Academic libraries increasingly provide research consultation services to support researchers, lecturers, and students throughout the research process. However, these services may remain fragmented, making it difficult for stakeholders to identify, access, and continue the support they need. This study aimed to map stakeholder user journeys, identify service gaps and pain points, and formulate opportunities for improving academic library research consultation services. A qualitative case study was conducted at the Library of Universitas Sebelas Maret, Indonesia. Data were collected through a focus group discussion involving 23 participants and semi-structured interviews with seven informants, comprising two lecturers, one student, one information technology staff member, and three librarians, complemented by observation and document analysis. The data were analyzed thematically to identify recurring patterns across stakeholder experiences. The findings revealed seven interconnected stages of the research consultation journey and five major service gaps involving service visibility, information access, consultation requests, service continuity, and follow-up. Based on these findings, the study developed a User Journey-Based Service Improvement Model connecting stakeholder research needs with accessible consultation, appropriate expertise, responsive support, documentation, feedback, and continuous improvement. The model provides an operational basis for developing more integrated, responsive, and stakeholder-centered research consultation services.